Антропологічні риси творців трипільської культури - Сегеда, С. (Народна творчість та етнографія, 2005)
The first notes and thoughts on the people of the Tryp³llyà are connected with the name of its opener Vikenty Khvoykà, who in 1902 found in village Verem'e in Middle Naddnipryanshñhyna burned human scalp, which was later investigated by Russian anthropologist G. Debets. By the absence of any kind of human bones from this era makes it impossible to figure out anthropological build of the humans of the Early Tryp³llyà culture. It creates a lot of assumptions around possible components of this type of anthropological build. It can only be proved that people from Tryp³llyà tribes which for thousands of years were functioning on the lands of contemporary Ukraine played an important role in the formation of the genetic foundation of the autochthonic ethnos of the South of East Europe, which we consider to be the ancestors of Ukrainian folk.